Watkins and Kamp Families in Huntington Beach - Watkins, Howard::::::::: (1988)
Front: Robin Watkins and Adam Watkins; Back: Albert Watkins wearing Cherokee Indian headdress, Frances Kamp, Jerry Kamp and Carol, Howard Watkins, and Rose O'Reilly